2018
DOI: 10.1007/s40256-018-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Stent Thrombosis in Patients with Versus Without Diabetes Mellitus Following Percutaneous Coronary Intervention with Drug-Eluting Stents: A Systematic Review and Meta-Analysis

Abstract: Both patients with and without diabetes mellitus had a similar rate of early stent thrombosis following PCI with DES. However, diabetes mellitus was associated with a significantly higher rate of late stent thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…That study also found a higher 2-year incidence of stent thromboses in patients with diabetes (1.0 %), but not with prediabetes (0.6 %), as compared to patients with normoglycemia (0.5 %) [ 23 ]. A meta-analysis that assessed stent thrombosis following PCI with DES showed that 5123 patients with diabetes had a higher late stent thrombosis rate than 13,775 normoglycemic patients [ 27 ]. The increased stent thrombosis risk in patients with diabetes may in part be related to their hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…That study also found a higher 2-year incidence of stent thromboses in patients with diabetes (1.0 %), but not with prediabetes (0.6 %), as compared to patients with normoglycemia (0.5 %) [ 23 ]. A meta-analysis that assessed stent thrombosis following PCI with DES showed that 5123 patients with diabetes had a higher late stent thrombosis rate than 13,775 normoglycemic patients [ 27 ]. The increased stent thrombosis risk in patients with diabetes may in part be related to their hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…The E‐Five registry, a prospective multicenter all‐comers registry of over 8000 patients assessing the efficacy of the endeavor stent, showed patients with DM had increased rates of definite or probable ST at 30 days compared with those patients without DM (1.1% vs. 0.6%, p = 0.015) 4 . However, these results have not been replicated in pooled analyses, with one study demonstrating no increase in the risk of early ST in patients with DM (OR 1.30, 95% confidence interval [95% CI] 0.89–1.91) 5 . Thus, the existing literature is conflicting and it remains unknown whether the presence of DM is associated with an increased risk of early ST.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, these results have not been replicated in pooled analyses, with one study demonstrating no increase in the risk of early ST in patients with DM (OR 1.30, 95% confidence interval [95% CI] 0.89-1.91). 5 Thus, the existing literature is conflicting and it remains unknown whether the presence of DM is associated with an increased risk of early ST.…”
Section: Introductionmentioning
confidence: 99%
“…The network meta-analysis by Philip et al, in 2016, affirmed a marked reduction in ST events in PCI patients who received drug-eluting stents [ 11 ]. The systematic review and meta-analysis by Yuan and Xu, in 2018, alternatively confirmed a similar ST rate among diabetic and non-diabetic PCI patients [ 12 ]. The study by Hara et al, in 2021, precisely underscored the lack of adequate prediction models to discriminate between ST risk scores and bleeding predisposition in patients undergoing PCI [ 13 ].…”
Section: Introductionmentioning
confidence: 99%